2016
DOI: 10.3390/catal6100152
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Removal of Trichloroethylene in Water Using Nano-ZnO/Polybutadiene Rubber Composites

Abstract: An innovative nanoscale ZnO/polybutadiene rubber composite (ZBRC) was developed as a valid alternative to TiO 2 particles or immobilized TiO 2 for the mineralization of chlorinated hydrocarbons without difficulties in the recovery of nanoscale photocatalyst particles. A synergistic increase in the removal of 1,1,2-trichloroethylene (TCE) through the coupled reaction processes (i.e., sorption, photolysis, and photocatalysis) was observed because sorption of TCE to the ultraviolet(UV)-transparent polybutadiene r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Inhibition of the degradation process with high initial crotamiton concentrations may be attributed to competition from intermediates produced by crotamiton degradation [37]. Jang et al, found that the target material (trichloroethylene) saturated the composite catalyst surface and reduced photon efficiency, leading to photocatalyst deactivation [45]. Kuo et al, showed that the degradation rates of codeine and methamphetamine increased with increasing initial concentration (100-250 µg/L) [44,46].…”
Section: Adsorption and Photocatalytic Degradation Of Crotamiton By Tmentioning
confidence: 99%
“…Inhibition of the degradation process with high initial crotamiton concentrations may be attributed to competition from intermediates produced by crotamiton degradation [37]. Jang et al, found that the target material (trichloroethylene) saturated the composite catalyst surface and reduced photon efficiency, leading to photocatalyst deactivation [45]. Kuo et al, showed that the degradation rates of codeine and methamphetamine increased with increasing initial concentration (100-250 µg/L) [44,46].…”
Section: Adsorption and Photocatalytic Degradation Of Crotamiton By Tmentioning
confidence: 99%
“…Despite this, better results were obtained with our Fe catalyst in comparison with the others described in the literature [36]. Furthermore, in the case of ZnO@CALB, the addition of hydrogen peroxide as an oxidant improved the degradation capacity of the catalyst from 41 to more than 80% in 5 min (Table 1, entries 11 and 15), which represent in both cases an improvement compared with other ZnO nanoparticles described in the literature [37].…”
Section: Trichloroethylene (Tce) Degradation Catalyzed By Menps@calb mentioning
confidence: 53%